Cd99l2 regulates excitatory synapse development and restrains immediate-early gene activation - Minji Kang; Sang Ho Yoon; Minkyung Kang; Seung Pyo Park; Woo Seok Song; Jungho Kim; Seungha Lee; Da-ha Park; Jae-man Song; Beomsue Kim; Kyung Hee Park; Eun-Hye Joe; et al. (Cell Reports)
Summary: Cd99 molecule-like 2 (Cd99l2) is a type I transmembrane protein that plays a role in the transmigration of leukocytes across vascular endothelial cells. Despite its high expression in the brain, the role of Cd99l2 remains elusive. We find that Cd99l2 is expressed primarily in neurons and positively regulates neurite outgrowth and the development of excitatory synapses. We demonstrate that Cd99l2 inversely regulates the expression of immediate-early genes (IEGs), including Arc, Egr1, and c-Fos, by inhibiting the activity of the transcription factors CREB and SRF. Neuronal inactivation increases the transport of Cd99l2 to the cell surface from recycling endosomes, thereby enhancing Cd99l2-mediated inhibitory signaling. Additionally, Cd99l2 knockout mice exhibit impaired excitatory synaptic transmission and plasticity in the hippocampus, along with deficits in spatial memory and contextual fear conditioning. Based on these findings, we propose that neuronal Cd99l2 functions as a synaptic cell adhesion molecule that inversely controls neuronal activation.